Phase 2 placebo-controlled, single-blind trial to evaluate the impact of oral ibandronate on bone mineral density in osteopenic breast cancer patients receiving adjuvant aromatase inhibitors: 5-year results of the single-centre BONADIUV trial. (February 2019) - Livi, Lorenzo; Scotti, Vieri; Desideri, Isacco; Saieva, Calogero; Cecchini, Sara; Francolini, Giulio; Becherini, Carlotta; Delli Paoli, Camilla; Visani, Luca; Salvestrini, Viola; De Feo, Maria Laura; Nori, Jacopo; et al.
Abstract: Aim: We present the final results of the BONADIUV trial, a single-blind, randomised, placebo-controlled phase 2 study to evaluate the impact of ibandronate treatment on bone mineral density (BMD) in osteopenic women taking aromatase inhibitors (AI). Patients and methods: Between 2011 and 2014, 171 osteopenic patients were randomised in a 1:1 ratio to receive either placebo or oral monthly ibandronate (150 mg). Treatment duration was 2 years, with 6-month evaluation. Primary end-point was the 2-year lumbar spine (LS) and total hip (TH) T-score mean differences as measure of BMD variation. Secondary analyses of survival outcomes have been performed at a 5-year median follow-up. ClinicalTrials.gov identifier: NCT02616744. Results: Median age of study population was 60.2 years (range 44–75). At the database cut-off time, the median follow-up was 63.3 months (range 2.7–87.3). No difference in terms of T-score was shown at baseline between arms both for TH ( P  = 0.61) and LS ( P  = 0.96). At 2-year follow up, the mean change was statistically significant in favour of ibandronate arm both at TH ( P  = 0.0002) and LS ( P  < 0.0001). No significant difference in terms of adverse events was observed between arms. At a median follow-up of 63.3 months (range 2.7–87.3), the overall survival (OS) rate was 97.5% in the placebo group and 93.0% in the ibandronate arm ( P  = 0.19). The invasive disease-free survival (iDFS) rates did not differ between groups ( P  = 0.42). Conclusions: Ibandronate compared to placebo improved BMD change in osteopenic women treated with adjuvant AI. Five-year survival analyses showed no difference between arms in terms of OS and iDFS rates. Highlights: Bisphosphonates prevent bone loss in adjuvant osteopenic breast cancer patients. A bone loss prevention strategy for patients receiving adjuvant AI is crucial. Longer follow-up and further investigations are warranted.